PENGUATAN LITERASI KEUANGAN DAN JIWA KEWIRAUSAHAAN SYARIAH SEBAGAI UPAYA MEMBANGUN KESADARAN EKONOMI BERKELANJUTAN BAGI KALANGAN GENERASI MUDA DI BLUTO SUMENEP - Holilurrahman, Holilurrahman; Azimah, Asfiatul (Universitas Al-Amien Prenduan, 2024)
The issue behind this activity is the young generation's lack of understanding of financial literacy, especially that based on sharia principles. Many young people lack awareness of how to manage their personal finances wisely and have little interest in entrepreneurial activities oriented towards economic sustainability and Islamic values. This situation necessitates efforts to educate the younger generation so that they have the knowledge and skills to manage their finances and are able to innovate in the field of sharia entrepreneurship. The community service method was carried out through a participatory approach with workshops, interactive training, and business assistance based on sharia values. This activity involved participants from among students and rural youth who were given material on sharia financial management, halal business planning, and community-based micro-business development strategies. An educational and practical approach was used to encourage active participant involvement and foster a spirit of economic independence based on Islamic values. The results of this community service activity showed a significant increase in participants' knowledge and attitudes towards the importance of financial literacy and Islamic entrepreneurship. Participants became more aware of the importance of managing finances ethically, economically, and productively, and began to develop ideas for small businesses based on local potential. Additionally, a collective awareness grew to build a sustainable community economy through Islamic principles. This program is expected to serve as a model for nurturing the economic development of the younger generation, balancing spiritual, social, and economic values in the Bluto area and its surroundings.